Transformation of New Student Admissions Policy from PPDB to SPMB: Rhetoric or Substantive Policy? - Latief, Suryawahyuni; Putri, Elza Eka; Khairan, Khairan; Thepmondhari, Rangsan; Hua, Wu Hui (Studies in Learning and Teaching, 2025)
This research explores the policy transformation of student admission from Penerimaan Peserta Didik Baru (PPDB) to Seleksi Penerimaan Murid Baru (SPMB) through the lens of rhetoric or substance. It investigates whether this shift reflects genuine policy reform or merely rhetorical packaging. This study used a qualitative descriptive approach; the research collected data through observation, in-depth interviews, and analysis of policy documents related to student admission practices. This study was conducted at two public junior high schools in the central area of Jambi City. The findings reveal that the transformation from the PPDB to SPM is not fully substantive; rather, it functions largely as a rhetorical response to public pressure. Nevertheless, the SPMB policy introduces several procedural adjustments, including greater flexibility in technical guidelines and modifications to the transfer pathway. These findings suggest the need for more comprehensive reforms to ensure that policy changes meaningfully improve equity and transparency in new student admission.